Efektivitas Model Pembelajaran kooperatif Tipe Script dalam Pembelajaran Membaca Pemahaman Siswa Sekolah Dasar - Warda; Sulfasyah; Tasrif Akib (Pusat Pengembangan Pendidikan dan Bakat Indonesia, 2022)
The research objective was to find out how the results of learning Indonesian using the Script Type Cooperative learning model are a type of research that only involves one class as an experimental class which is carried out without a comparison group. Data collection techniques used are observation and tests in the form of essays. The results showed that the use of the script type cooperative learning model for learning reading comprehension in positive students was better than before using the script cooperative model. the results of inferential statistical analysis using the t-test formula and it is known that the value of Tcount obtained is Tcount = 26.798 and Ttable = 2.05954, so Tcount > Ttable or 26.798 > 2.05954. So it can be concluded that Ho (no influence) is rejected and H1 (there is influence) is accepted. This proves that there is an effect of using the script type cooperative learning model on learning reading comprehension in class V UPT SPF SDN Maccini Sombala.